2022
DOI: 10.1101/2022.09.21.508836
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metamorphic proteins at the basis of human autophagy initiation and lipid transfer

Abstract: Autophagy is a conserved intracellular degradation pathway that uses de novo double-membrane vesicle (autophagosome) formation to target a wide range of cytoplasmic material for lysosomal degradation. In multicellular organisms, autophagy initiation requires the timely assembly of a contact site between the ER and the nascent autophagosome. Here, we report the in vitro reconstitution of a full-length seven-subunit human autophagy initiation super-complex and found at its core ATG13-101 and transmembrane protei… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 67 publications
1
17
1
Order By: Relevance
“…It is important to note the absolute number of ATG13 foci formed after autophagy induction (~30) is almost double of the other autophagy factors tested (~10-15), suggesting that ATG13 is one of the first autophagy factors recruited to ATG9 vesicles. This is consistent with the recently observed interaction between ATG13 and ATG9 [66][67][68] This work also suggested that ATG13 binds to two distinct regions in ATG9, one independent of ATG101 and a second promoted by an ATG101 induced conformational change in the HORMA domain of ATG13 67,68 . Our results demonstrate that ATG13 is recruited to phagophores in the absence of ATG101, potentially reflecting ATG13 binding to the ATG101 independent binding site on ATG9.…”
Section: Atg13 Recruitment To Phagophores Is Independent Of Atg101 An...supporting
confidence: 92%
See 2 more Smart Citations
“…It is important to note the absolute number of ATG13 foci formed after autophagy induction (~30) is almost double of the other autophagy factors tested (~10-15), suggesting that ATG13 is one of the first autophagy factors recruited to ATG9 vesicles. This is consistent with the recently observed interaction between ATG13 and ATG9 [66][67][68] This work also suggested that ATG13 binds to two distinct regions in ATG9, one independent of ATG101 and a second promoted by an ATG101 induced conformational change in the HORMA domain of ATG13 67,68 . Our results demonstrate that ATG13 is recruited to phagophores in the absence of ATG101, potentially reflecting ATG13 binding to the ATG101 independent binding site on ATG9.…”
Section: Atg13 Recruitment To Phagophores Is Independent Of Atg101 An...supporting
confidence: 92%
“…Our results demonstrate that ATG13 is recruited to phagophores in the absence of ATG101, potentially reflecting ATG13 binding to the ATG101 independent binding site on ATG9. The slow kinetics for this interaction observed in vitro 67 , might be overcome by the high expression levels of ATG13 in cells 9 , assuring that the number of ATG13 molecules in a conformation capable of binding ATG9 is sufficiently high at all times. The increase in the number of ATG13 foci under amino acid or glucose starvation suggests that the interaction between ATG9 and ATG13 is promoted under these conditions potentially by phosphorylation of ATG9 or ATG13 69 (Fig.…”
Section: Atg13 Recruitment To Phagophores Is Independent Of Atg101 An...mentioning
confidence: 99%
See 1 more Smart Citation
“…This raises the possibility that something else could be captured by the seatbelt or that the seatbelt mechanism is rather used allosterically by stabilizing different conformers. Regardless, the change in structure and surface charge due to metamorphosis allows conformers to be separated using anion exchange chromatography [46,68,73,76,78]. Wildtype ATG13 elutes as a single (default) conformer, which indeed promptly binds ATG101 but requires a long incubation with ATG9A N before interacting.…”
Section: Atg13 and Atg101 Metamorphosis In Human Autophagy Initiationmentioning
confidence: 99%
“…Consistent with this notion, Atg9/ATG9A lipid scramblase mutants show a defect in phagophore expansion [ 68 , 69 ], and recent in vitro experiments have revealed that Atg9 stimulates the Atg2-Atg18 complex-mediated lipid transfer to the acceptor membrane [ 70 ]. Moreover, evidence suggests that ATG9-ATG13-ATG101 is central to the formation of a super-complex with the ULK kinase and PI3K complexes, which enhances the action of the ATG2-WIPI4 complex as a tether and lipid transfer protein at the phagophore-ER MCSs [ 71 ].…”
Section: Mcss During Autophagosome Biogenesismentioning
confidence: 99%